Promoting equity, cooperation and innovation in the fields of transboundary waters and natural resources management : the legacy of Dr. David J.H. Phillips - Phillips, David J. H. (International water law series ;, 2017)
Promoting Equity, Cooperation and Innovation in the Fields of Transboundary Waters and Natural Resources Management' honours the memory and legacy of Dr. David J.H. Phillips, an extraordinary scientist, consultant and friend of the editors and contributors. He was a scientist of exceptional quality, dedicated to the practical study of aquatic environments, be they marine, freshwater or virtual. This volume contains excerpts from his meticulously researched work from a wide range of settings globally. Colleagues' essays provide insights to a man who lived life to the utmost, worked to the highest professional standards and had a unique gift in challenging situations to generate understanding and practical responses through his curiosity, remarkable ingenuity, and sheer hard work. His work opens many new paths of research and continues to inspire scientists and researchers in the fields of marine biology and pollution, fresh water issues, and conflict over transboundary water resources.